Improving Employee Performance through Achievement Motivation and Organizational Learning with The Mediation Role of Innovative Work Behavior - Legiman, Legiman; Widayati, Tri (Faculty of Economics and Business UNTAG Semarang, 2024)
The government organizations must strive to improve employee performance by optimizing the potential of each employee. Therefore, the current study aims to analyze the effect of achievement motivation and organizational learning on employee performance with the mediating role of innovative work behavior. The sample size was taken from 93 employees of Pemalang District Village, Pemalang Regency, Central Java, Indonesia. The collected data were tested using Partial Least Square. The finding revealed achievement motivation and organizational learning have a positive effect on employee performance. Furthermore, the results prove that innovative work behavior can mediate the relationship of achievement motivation and organizational learning on employee performance. The importance of these results contribute to supporting human resource management theories.